Fortran for Today and Tomorrow - Pressman, Michael H. (Wm. C. Brown Publishers, 1993)
Fortran for Today and Tomorrow is designed as an introduction to this oldest of high-level computer languages, a language that, despite the predictions of its demise many years ago, continues to be used extensively$1! =s
Keywords: Computer Language; Non-Fiction